Effective treatment of refractory, locally metastatic squamous cell carcinoma of the leg with isolated limb perfusion: a case report with unexpected long progression-free interval - Kanatoula, Danai-Dionysia; Wohlfeil, Sebastian A.; Jakob, Jens; Hohenberger, Peter; Utikal, Jochen (Frontiers in oncology, 2025)
Non-melanoma skin cancer (NMSC) is one of the most commonly diagnosed human malignancies and its incidence is steadily increasing. Locally advanced cutaneous squamous cell carcinoma of the extremities that is refractory to standard therapies can be challenging to treat, with amputation of the limb being the ultima ratio treatment. Here we present a 67-year-old female patient with metastatic SCC of the leg refractory to standard therapies who was effectively treated with isolated limb perfusion and is free of any sign of relapse since more than 3 years. This case report provides a brief review of the recent literature on isolated limb perfusion and how this effective treatment can preserve the patient’s quality of life by avoiding radical surgery and its negative consequences through limb salvage.
Gesehen am 10.07.2025